An Appraisal of the Legal Framework Governing the Admissibility of Electronic Documents as Evidence in Malaysian Shariah Courts: Current Practices and Future Legal Directions - Mohamad Aniq Aiman Alias; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Hasnizam Hashim; Muzaffar Syah Mallow (IIUM Press, 2026)
Indexed by Scopus/MyCite